Sha'irat Mu'asirat - Jarrar, Husni Ad'ham (Amman : Mu'assasah al-Zaytunah Lil Nashr, 2001)
Contemporary Arab poetess ; biographies
Keywords: Women poets, Arab -- Biography; Arabic poetry -- Women authors -- Biography